Spelling errors and social media outrage: on the Conservative Party of Canada’s error-ridden pamphlet - Sweet, T. Andi (My University, 2021)
The age of social media permanently changed the way voters engage with elections. At the centre of this change, a Conservative Party of Canada mailer riddled with errors became the focus of a debate: were the errors the result of an ineffectual copyeditor, or were they something else? In looking at the 2021 Election as a whole, it becomes clear that spelling errors in the doorknocker were not only intentional but part of a larger strategy built to stew outrage and further stoke divide between Canada’s political parties.
Keywords: elections; social media